2012
DOI: 10.1002/hlca.201200032
|View full text |Cite
|
Sign up to set email alerts
|

Chirality Transfer in the Formation of Poly(oxymethylene) Helices by Anionic Polymerization

Abstract: In this article, we present the synthesis of a series of oligo(oxymethylenes) capped with 1‐phenylethanol and MeOH. The anionic condition affords enantiomerically pure oligo(oxymethylene) oligomers, while the cationic oligomerization leads to a racemic mixture of the oligo(oxymethylene) chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In one experiment significant asymmetric 1,10-induction of chirality was obtained in a Grignard reaction along the oxymethylene chain [ 80 ]. Experiments also showed that our diastereoselectivity rule also applied across an oligomeric polyoxymethylene chain [ 79 , 81 ]. In fact the helical conformation of the -O-C-O- sequence in polyformaldehyde resembles rather the atomic arrangement of -O-Si-O- helices in a quartz crystal or atomic arrangements in other inorganic crystals [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one experiment significant asymmetric 1,10-induction of chirality was obtained in a Grignard reaction along the oxymethylene chain [ 80 ]. Experiments also showed that our diastereoselectivity rule also applied across an oligomeric polyoxymethylene chain [ 79 , 81 ]. In fact the helical conformation of the -O-C-O- sequence in polyformaldehyde resembles rather the atomic arrangement of -O-Si-O- helices in a quartz crystal or atomic arrangements in other inorganic crystals [ 79 ].…”
Section: Discussionmentioning
confidence: 99%